The influence of adiabatic heat and combined blast load and fire loading on the response of mild steel plates - Nurul Syafiqah, Abdul Razak; Nik Nur Atif Arisya, Nik Mazlan; Zulkafli, Hassan; Aizat, Alias (Institute of Physics, 2023)
This paper study the influence of adiabatic heat and fire loading on the behaviour of unstiffened mild steel plates subjected to close-in blast loads using finite element (FE) analysis. A quarter-symmetry 3D FE model consists of the steel plate, clamps and bolts was developed using Abaqus/CAE. Classical plasticity model was used as the material model in the steel plate and bolts. The clamps were assumed as an elastic material. Temperature-material properties relationship according to Eurocode 3 and Masui model was assigned to the steel plate. Conwep function was used to simulate the blast loads. The influence of strain rates was considered in the steel plate using the Cowper-Symonds equation. The FE model of the unstiffened plates was verified and validated against experimental data from literature, where a good agreement was achieved. The results suggest the adiabatic heat in the steel plates does not significantly influence the behaviour of the steel plates in both temperature-material properties models. The study then investigated the effect of combined blast loads and fire loading on the response of steel plates. The fire loading was applied by increasing the temperature in the steel from 200 °C to 1000 °C. Excessive deformation and thinning of the plate at the central area of the plate was observed. The thinning at the central area is pronounce than the thinning of the plate at the boundary between the clamp and the steel plate. Hence, the FE analysis suggests that the failure might occur at the central area of the plate, which could suggest a tearing type of failure. This type of failure is common in plates subjected to close-in blast loads. Therefore, this study has shown that the effect of adiabatic heat is insignificant, and the combined blast-fire loading might cause a similar type of failure as in plates subjected to blast loads only.